Pengembangan Media Musikalisasi Puisi Terhadap Kemampuan Mengapresiasi Puisi Siswa Kelas X SMA Swasta Al-Hidayah Medan - Nasution, Salsabillah Nur Izza; Amaluddin, Amaluddin; Ali, Ali (Medan Resource Center, 2025)
This study aims to develop an audio-visual-based poetry musicalization media to enhance students’ poetry appreciation skills in 10th-grade senior high school students. The research employs the Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The study evaluates the effectiveness of this media in fostering student engagement and comprehension in poetry learning. The findings indicate a significant improvement in students' poetry appreciation skills, with their average scores increasing from 66.8 to 81.1. Additionally, students provided positive feedback, reporting heightened interest and motivation in learning poetry through this approach. Teachers also acknowledged the media’s role in creating a more dynamic and interactive learning environment. These results suggest that poetry musicalization media serves as an effective alternative for improving literary learning in schools, fostering a deeper understanding and appreciation of poetry among students, and enhancing the overall engagement in Indonesian language learning.